Research of the Driving Characteristic of Differential-drive Adaptive Pipe Robot - Wang Chenzhong; Wang Ting; Liu Jun; Zhang Zhaolong; Hu Shaogang (Jixie chuandong)
Aiming at solving the problems of relative sliding between the robot driving wheel and the tube wall and the adaptation of the robot body to the pipe diameter,the pipe robot with the characters of autonomous differential motion and adaptive variable diameter is designed by adopting the single motor to drive. The transmission characteristics of the differential mechanism are analyzed,the force equation of working state for the variable diameter mechanism of pipe robot is theoretically deduced,and the mechanical relation between the driving wheels and pipe wall in robot operation is obtained. The movement model of robot in pipe is built,and the relationship between each variable in the model under the condition of different pose is analyzed. The virtual prototype model of robot operating in combined pipe is built through the simulation analysis. The robot characters of autonomous differential motion is validated. The results indicate that the pipeline robot can through bends without interference,and show a good driving characteristics.